The Engineer. English Language for Industrial Engineering - Casañ Pitarch, Ricardo (Académica, 2023)
The Engineer: English Language for Industrial Engineering is a book with a serious video game that aims at teaching students general English at B2 level (CEFRL) and technical language related to the industrial engineering business. The book contains six units contextualized in the story of a recently graduated industrial engineer who is looking for a first engineering job. The book and the video game provide an environment of linguistic immersion through functional language, reading comprehension, and the protagonist's interaction with other computerized characters. The new knowledge is introduced in the teaching book and practiced along with the corresponding missions of the video game. The exercises are related to the industrial engineering industry and are based on puzzles, tests, fictional dialogues, search and use of objects, and other skill games. This material aims to make the learning process more engaging with active exercises immersed in the fictional reality of a video game.